Prevention Messages in Parent-Infant Bed-Sharing: Message Source, Credibility, and Effectiveness. (16th November 2017) - Austin, Jillian E.; Nashban, Chad J.; Doering, Jennifer J.; Davies, W. Hobart
Objective . Despite educational outreach, bed-sharing prevalence is rising. Mothers' and fathers' bed-sharing practices, prevention message source, perceived source credibility, and the effectiveness of the prevention message were evaluated. Methods . Data were collected from 678 community parents via an online survey. Results were analyzed using descriptive statistics and phi tests. Results . Bed-sharing reasons focused on comfort and ease. Mothers were more likely to receive prevention messages from individual professionals or organizations, whereas fathers were more likely to hear prevention messages from spouses/coparents and grandfathers. Physicians were the most common source, and physicians and grandmothers were rated as the most credible and effective. Conclusions . Prevention message source varies between mothers and fathers, highlighting the need for continued research with fathers. Grandmothers and physicians are effective and credible sources of prevention messages. Although less frequent, prevention messages from grandmothers were most effective. There was no evidence of effective messages from educational campaigns.